Estimativas y prospectivas sobre el sistema jurídico ambiental peruano post-Río + 20 - Foy Valencia, Pierre (2013)
This article is intended to explain core ideas resulting from processes of which Peruvian environmental legal system is derived; it is morean overview rather than a system characterization, as well as a perspective or sampling foresight representing Río +20 process meaning. In that sense, it examines the modern environmental regulations rising context and provides a brief retrospective of Peruvian environmental legal system development and prospective studies within the frame of green economy paradigms and the environmental governance, presenting only three prospective references aschallenges and trends on: Climate and Energy Law, a new legal Framework for a Green Economy and Sustainable Enterprise, and finally, stressing emphatically on mega-cities, Conurbation and Land use Planning issues given little attention usually law renders to this matters.